The great vandal scandal - Ecton, Emily (Ecton, Emily, Great Pet Heist, 2023)
The animals of the Strathmore building have a mission--convince the raccoons who have invaded the loading dock to leave the building before Biscuit, the Yorkie on the second floor, is evicted for his non-stop barking, and Madison, Butterbean's human, is blamed for the destruction the raccoons are causing.